1979
DOI: 10.1103/physrevlett.42.739
|View full text |Cite
|
Sign up to set email alerts
|

Logarithmic Corrections in the Magnetic Equation of State for LiTbF4

Abstract: Using SQUID (superconducting quantum interference device) detection, the field and temperature dependence of the magnetization m has been measured close to the critical point of this uniaxial dipolar-coupled ferromagnet. It is shown for the first time that the Landau expansion of the field h holds if m is scaled by [liiidm/dh)/^] 1^* while other equations (of Ising, mean field) yield less agreement and unrealistic parameters. The expansion coefficients of the present analysis can explain in detail formerly mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, the constitutive dipoles interact via dipole-dipole interactions which are longranged, anisotropic and alternating in sign. Experiments have revealed that these can lead to the formation of unusual morphologies which significantly affect systemic behavior [1][2][3][4][5][6]. Disorder is another inherent feature of these systems due to the presence of defects and impurities.…”
mentioning
confidence: 99%
“…However, the constitutive dipoles interact via dipole-dipole interactions which are longranged, anisotropic and alternating in sign. Experiments have revealed that these can lead to the formation of unusual morphologies which significantly affect systemic behavior [1][2][3][4][5][6]. Disorder is another inherent feature of these systems due to the presence of defects and impurities.…”
mentioning
confidence: 99%
“…Using renormalization group arguments, Larkin and Khmelnitskii [8] and Aharony [9] showed that d * = 3 is the upper critical dimension for mean-field critical behaviour in a dipolar ferromagnet. This observation led to significant experimental efforts to find the expected logarithmic corrections to mean-field theory in LiHoF 4 [10,11,12,13,14]. The demagnetization field also renders the ferromagnetic transition quite peculiar in the presence of dipolar interactions [4] as these oppose a uniform magnetization and leads to the formation of domains below the transition [5,15].…”
mentioning
confidence: 99%
“…14)], LiTbF4 offers two fortunate features for this purpose due to the high quality of the crystals: (i) The critical temperature can be approached to f~10~4 (Ref. 15) without running into rounding phenomena and (ii) the material may be shaped to spheroids of thickness D between 0.1 and 10 mm with well-defined demagnetization coefficients TV. This allows a first serious test of the significant size effect on Yd predicted by the relaxational-wall model.…”
mentioning
confidence: 99%